Screening techniques for host plant resistance to cowpea insect pests - Jackai, L.E.N.; Singh, S. (1988)
As research on food crops intensifies in the tropics, the spotlight is being increasingly focused on the development of varieties with resistance to pests and diseases. Much of the time, money and patience needed to conduct research on host plant resistance (HpR) is spent on the development of methodologies that are eventually used to screen germplasm and breeding lines. The products of this screening provide the building blocks for the development of resistant varieties. Methodologies differ from one place to another and from one crop to the other, and are usually tailored to suit local and/or individual circumstances. There is, however, a need to develop standardized methodology to make comparisons across locations easier. Any methodology is capable of improvement, but improvements come only after use and evaluation. In this paper we try to define the current status of HPR screening methodology in cowpea entomology, concentrating mainly on techniques developed and used with considerable success at IITA. In addition, the shortcomings of some of these techniques are pointed out and areas needing improvement indicate.